2010
DOI: 10.1007/s10620-010-1380-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density, Vitamin D, and Disease Activity in Children Newly Diagnosed with Inflammatory Bowel Disease

Abstract: Serum vitamin D level is significantly lower in children with newly diagnosed IBD compared to those without. However, vitamin D levels are not affected by disease severity. It seems that BMD status may not be affected by vitamin D levels or disease severity in this cohort. Larger prospective controlled studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 17 publications
5
69
4
Order By: Relevance
“…This was documented for both children with IBD (e.g., Ref. 34) as well as in many studies with adult IBD patients (e.g., Ref. 61).…”
Section: Vitamin D Status In Ibdmentioning
confidence: 55%
“…This was documented for both children with IBD (e.g., Ref. 34) as well as in many studies with adult IBD patients (e.g., Ref. 61).…”
Section: Vitamin D Status In Ibdmentioning
confidence: 55%
“…No correlation between vitamin D levels and disease activity was observed in two cross-sectional studies (4,21) while a retrospective study concluded that vitamin D deficiency was associated with increased disease activity in patients with CD, but not with UC (33) . A recent study prospectively analyzed the association between vitamin D deficiency and the need for IBD-related surgery or hospitalizations in a large cohort of 3,217 patients and concluded that vitamin D deficiency was associated with an increased risk of surgery and hospitalization compared with those patients with adequate vitamin D levels (2) .…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies which have focused on vitamin D and its effect on clinical markers such as CDAI (a research tool used to quantify the symptoms of patients with Crohn's disease) and inflammatory markers have been inconclusive. In crosssectional IBD cohort studies El-Matary et al (81) and Hassan et al (42) reported no association between 25(OH)D and CDAI. CDAI levels <150 are indicative of remission, whereas levels above that suggest active disease.…”
Section: Vitamin D and Immune Function In Crohn's Disease: Experimentmentioning
confidence: 95%